The Effect of Dexmedetomidine in Combination with Bupivacaine on Sensory and Motor Block Time and Pain Score in Supraclavicular Block - Shahryar Sane; Shahram Shokouhi; Parang Golabi; Mona Rezaeian; Behzad Kazemi Haki (Pain Research and Management, 2021)
Background. Brachial plexus block is frequently recommended for upper limb surgeries. Many drugs have been used as adjuvants to prolong the duration of the block. This study aimed to assess the effect of dexmedetomidine with bupivacaine combination and only bupivacaine on sensory and motor block duration time, pain score, and hemodynamic variations in the supraclavicular block in upper extremity orthopedic surgery. Methods. This prospective, double-blind clinical trial study was conducted on 60 patients, 20 to 60 years old. Patients were candidates for upper extremity orthopedic surgeries. The sensory and motor block were evaluated by using the pinprick method and the modified Bromage scale. The postoperative pain was assessed by utilizing a visual analog scale. Results. The mean onset time of sensory and motor block in patients receiving only bupivacaine was, respectively, 31.03 ± 9.65 min and 24.66 ± 9.2 min, and in the dexmedetomidine receiving group, it was about 21.36 ± 8.34 min and 15.93 ± 6.36 minutes. The changes in heart rate and mean arterial blood pressure were similar in both groups. The duration of sensory and motor block and the time of the first analgesia request in the intervention group were longer. Postoperative pain was lower in the intervention group for 24 hours (P = 0.001). Conclusion. Dexmedetomidine plus bupivacaine reduced the onset time of sense and motor blocks and increased numbness and immobility duration. Also, dexmedetomidine reduced postoperative pain significantly with the use of bupivacaine for supraclavicular blocks. Trial Registration. IRCT, IRCT20160430027677N15. Registered 05/28/2019, https://www.irct.ir/trial/39463.